Efektivitas Metode Pembiasaan pada Bidang Studi Pendidikan Agama Islam Melalui Media Buku - Setiyo Bakti (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
This study used qualitative research methods. Researchers collect data by conducting direct research on the object to be studied using various instruments, namely observation, interviews, and documentation. The data processing process, goes through three stages, namely reduction, data display, and data verification. The results of the study first found that MI Empat Lima, Kedungpring District, Lamongan Regency implemented habituation activities using the Student Habituation book media which contained PAI material and guidance from PAI teachers and homeroom teachers and carried out daily evaluations and at the end of each semester. The two effects are in the form of students being able to use the media easily through habituation books to support student habituation activities and increase student abilities and also student achievement in the field of Islamic Religious Education study. Third, there are supporting factors such as the common vision in implementing and succeeding the madrasa program in improving the quality of education in madrasas as well as the high ability and willingness of students and inhibiting factors such as students forgetting to bring student habituation books and also the ability of students to absorb different materials differently